Global patterns of resilience decline in vertebrate populations. (16th November 2021) - Capdevila, Pol; Noviello, Nicola; McRae, Louise; Freeman, Robin; Clements, Christopher F.
Abstract: Maintaining the resilience of natural populations, their ability to resist and recover from disturbance, is crucial to prevent biodiversity loss. However, the lack of appropriate data and quantitative tools has hampered our understanding of the factors determining resilience on a global scale. Here, we quantified the temporal trends of two key components of resilience—resistance and recovery—in >2000 population time‐series of >1000 vertebrate species globally. We show that the number of threats to which a population is exposed is the main driver of resilience decline in vertebrate populations. Such declines are driven by a non‐uniform loss of different components of resilience (i.e. resistance and recovery). Increased anthropogenic threats accelerating resilience loss through a decline in the recovery ability—but not resistance—of vertebrate populations. These findings suggest we may be underestimating the impacts of global change, highlighting the need to account for the multiple components of resilience in global biodiversity assessments. Abstract : The resilience of vertebrate populations is declining worldwide. Multiple threats are accelerating this loss of resilience.